2022
DOI: 10.1007/s42979-022-01067-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep Residual Neural Network for COVID-19 Detection from Chest X-ray Images

Abstract: The COVID-19 diffused quickly throughout the world and converted as a pandemic. It has caused a destructive effect on both regular lives, common health and global business. It is crucial to identify positive patients as shortly as desirable to limit this epidemic’s further diffusion and to manage immediately affected cases. The demand for quick assistant distinguishing devices has developed. Recent findings achieved utilizing radiology imaging systems propose that such images include salient data about the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…between June 2020 and P r e p r i n t 10 August 2022, which, combined with the dynamically changing epidemiological situation and related changing recommendations, the tool may require updates in the future, which is the purpose of the already planned follow up study. Also, the number of cases used to teach the network may have been a limitation; publicly available networks for identifying images like ResNet-50 (23) and GoogLeNet (24) were trained on tens of thousands of cases, significantly increasing their predictive capabilities (25). possible (17)(18)(19).…”
Section: Study Size 10mentioning
confidence: 99%
“…between June 2020 and P r e p r i n t 10 August 2022, which, combined with the dynamically changing epidemiological situation and related changing recommendations, the tool may require updates in the future, which is the purpose of the already planned follow up study. Also, the number of cases used to teach the network may have been a limitation; publicly available networks for identifying images like ResNet-50 (23) and GoogLeNet (24) were trained on tens of thousands of cases, significantly increasing their predictive capabilities (25). possible (17)(18)(19).…”
Section: Study Size 10mentioning
confidence: 99%
“…Other MLbased systems for COVID-19 diagnosis usually use CT scan readings. For example, neural networkbased systems make it possible to distinguish COVID-19 symptoms from other lung diseases (10), (43), (44).…”
Section: Figure 6 Key Roles Of ML Techniques and Datasets To Tackle T...mentioning
confidence: 99%
“…As of now, professionals from all across the world are working hard to fight against the disease. Many researchers and academicians published different articles describing methods for detecting COVID-19 using CXR images [18] , [19] , [20] , [21] , [22] . Using image processing on chest X-ray images, Hasoon et al suggested a method for classifying and early detecting COVID-19.…”
Section: Introductionmentioning
confidence: 99%